STK3 Suppresses Ovarian Cancer Progression by Activating NF-κB Signaling to Recruit CD8+ T-Cells - Xiangyu Wang; Fengmian Wang; Zhi-Gang Zhang; Xiao-Mei Yang; Rong Zhang (Journal of Immunology Research, 2020)
Serine/threonine protein kinase-3 (STK3) is a critical molecule of the Hippo pathway but little is known about its biological functions in the ovarian cancer development. We demonstrated the roles of STK3 in ovarian cancer. Existing databases were used to study the expression profile of STK3. STK3 was significantly downregulated in OC patients, and the low STK3 expression was correlated with a poor prognosis. In vitro cell proliferation, apoptosis, and migration assays, and in vivo subcutaneous xenograft tumor models were used to determine the roles of STK3. The overexpression of STK3 significantly inhibited cell proliferation, apoptosis, and migration of ovarian cancer cells in vitro and tumor growth in vivo. Bisulfite sequencing PCR analysis was performed to validate the methylation of STK3 in ovarian cancer. RNA sequencing and gene set enrichment analysis (GSEA) were used to compare the transcriptome changes in the STK3 overexpression ovarian cancer and control cells. The signaling pathway was analyzed by western blotting. STK3 promoted the migration of CD8+ T-cells by activating nuclear transcription factor κB (NF-κB) signaling. STK3 is a potential predictor of OC. It plays an important role in suppressing tumor growth of ovarian cancer and in chemotaxis of CD8+ T-cells.